UB Integrated Door-To-Door Health Clinic Model for Community Health Literacy And Cadre Empowerment - Dewi, Elvira Sari; Nurul Evi; Tri Yudani Mardining Raras; Linda Wieke Noviyanti; Muhammad Mumtaz Firdausi; Revania Angelina Putria Sidhikhoh; Navia Irfani Nabila; Achmad Andre Maulana; Restu Aisyah Rohma; Aufa Humayra Putrikami; Untari; Arfandeon Darrel Selva Reksa Priyanggada; Imam Wahyu Indrawan; Intan Yusuf Habibie; Cesarius Singgih Wahono; Nur Salim (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2026)
Low community health literacy and limited local health cadre capacity remain major public health challenges in peri-urban areas of Malang, Indonesia. To address these issues, Universitas Brawijaya (UB) developed the UB Integrated Door-to-Door Health Clinic Model, combining health education, basic medical services, and cadre empowerment through household-based outreach. This study evaluated the model’s effectiveness in improving community health literacy and cadre capacity in Kalirejo Village. The program involved lecturers, students, healthcare professionals, and local cadres through health education, screening, counseling, and training activities. Quantitative data were analyzed using descriptive statistics and paired comparative tests, while qualitative feedback was analyzed thematically. Results showed significant improvements in community health literacy mean scores (62.4% to 81.7%; p<0.05) and cadre competency scores (58.9% to 84.3%; p<0.05). Participants also reported increased engagement in health promotion activities. The model demonstrates the potential of university-led integrated outreach programs for sustainable community empowerment and health promotion.